KEARIFAN LOKAL DALAM CERITA RAKYAT LUBUKLINGGAU PROVINSI SUMATERA SELATAN - NFN Hasanadi (Balai Pelestarian Nilai Budaya Sumatera Barat, 2018)
This paper discusses the reflection of local wisdom within Lubuklinggau folklore of South SumatraProvince, namely the story of Linggau and Dayang Torek: the Origin of Lubuklinggau City, the story ofSilampari: the myth of the Ulak Lebar Kingdom, and the story of Bujang Kurap: Budiman, The PowerfulWanderer. By using hermeneutic approach, it is concluded that every expression contains local wisdomin the form of virtues and badness, reflected through theme, characterization and moral socio-culturemandate of Lubuklinggau community. The values of virtues are patience, learning determination,responsibility, responding evil with good deed, and prioritizing interests of society rather than personaland familial interests. Meanwhile, the evil attributes that must be avoided are arrogance, egoism,conspiracy in evil and uncontrolled emotion.